1. 2(x - 4) - 2x = 2x - 10
2. Distribute the 2: 2x - 8 - 2x = 2x - 10
3. Simplify and combine like terms: -8 = 2x - 10
4. Add 10 to both sides: -8 + 10 = 2x
5. Simplify: 2 = 2x
6. Divide both sides by 2: 2/2 = x
7. Simplify: 1 = x
Therefore, the correct answer is x = 1.
Drag and drop the correct steps to solve the equation for x. Make sure to put the steps in order. Not all steps listed will be used.
2(x - 4) - 2x = 2x - 10
8 = 2x - 10
- 8 = 2x - 10
2 = 2x
2x + 8 - 2x = 2x - 10
2x - 8 - 2x = 2x - 10
18 = 2x
x = 9
x = 1
1 answer